An Alternative for Conflict-Based Criminal Settlement Based on Positive Law and Islamic Law - Nurhidayat, Syarif; Ali, Mahrus; ., Sufriadi (KnE Social Sciences, 2023)
Procedural criminal law proceedings were seen to be ineffective and could even trigger a deeper conflict in Indonesia. This study aimed to identify an alternative for the settlement of criminal acts that originate from horizontal conflicts, based on positive law and Islamic criminal law, considering that Muslims make up the majority of the Indonesian population. This is crucial, considering Indonesia has more than 1,300 tribes and ethnicities. This study used a normative method with a philosophical and conceptual approach. The study results showed that, first, from the positive law perspective, criminal proceedings can be done through restorative justice, such as giving more attention to victims in the criminal justice process; penal mediation; peace; reconciliation, and political decisions. From the Islamic law perspective, settling by forgiveness; Islah; and political decisions are possible. Keywords: Alternative; Criminal Act; Conflict; Restorative Justice; Islam